Athlete biometric data in soccer: Athlete protection or athlete exploitation? - Garlewicz, A. (DePaul Journal of Sports Law, 2020)
This article is divided into three parts. Part I gives a synopsis of the current law in the United States dealing with the collection of biometric data. Part II provides an overview of how soccer is organized and regulated on an international level. Part III discusses the technology used in soccer to collect soccer players` biometric data and the legal issues that arise from the collection of biometric data.